miR-190a-5p Partially Represses the Abnormal Electrical Activity of SCN3B in Cardiac Arrhythmias by Downregulation of IL-2 - Li, Qianqian; Zhang, Ziguan; Chen, Shanshan; Huang, Zhengrong; Wang, Mengru; Zhou, Mengchen; Yu, Chenguang; Wang, Xiangyi; Chen, Yilin; Jiang, Dan; Du, Dunfeng; Huang, Yufeng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cardiac arrhythmias (CAs) are generally caused by disruption of the cardiac conduction system; interleukin-2 (IL-2) is a key player in the pathological process of CAs. This study aimed to investigate the molecular mechanism underlying the regulation of IL-2 and the sodium channel current of sodium voltage-gated channel beta subunit 3 (SCN3B) by miR-190a-5p in the progression of CAs. ELISA results suggested the concentration of peripheral blood serum IL-2 in patients with atrial fibrillation (AF) to be increased compared to that in normal controls; fluorescence in situ hybridization indicated that the expression of IL-2 in the cardiac tissues of patients with AF to be upregulated and that miR-190a-5p to be downregulated. Luciferase reporter assay, quantitative real-time-PCR, and whole-cell patch-clamp experiments confirmed the downregulation of IL-2 by miR-190a-5p and influence of the latter on the sodium current of SCN3B. Overall, miR-190a-5p suppressed the increase in SCN3B sodium current caused by endogenous IL-2, whereas miR-190a-5p inhibitor significantly reversed this effect. IL-2 was demonstrated to be directly regulated by miR-190a-5p. We, therefore, concluded that the miR-190a-5p/IL-2/SCN3B pathway could be involved in the pathogenesis of CAs and miR-190a-5p might acts as a potential protective factor in pathogenesis of CAs.